One Day, One Story: Cultivating a Love of Reading from an Early Age - Sri Utamimah; Bannaga Taha Elzubair Hussen (Early Childhood Development Gazette, 2024)
This research aims to examine the importance of an interest in reading from an early age in the hope of forming the nation's next generation with high quality and broad insight. A high interest in reading from an early age is an important foundation in forming a child's character and intellect. By reading, children can broaden their horizons and improve their qualities which will be beneficial for their future. One of the methods applied to foster interest in reading in young children is the "One Day One Story" activity, which is held every Monday to Friday. This research uses a qualitative descriptive approach with research subjects of early childhood aged 4-6 years. The data collection techniques used include observation, interviews and documentation to get an in-depth picture of the application and influence of the "One Day One Story" activity on children's interest in reading. The research results show that the implementation of the "One Day One Story" activity is effective in fostering interest in reading in young children. This can be seen from the children's enthusiasm in looking for story books and opening various book pages. Children become more interested in reading and exploring the stories provided. It is hoped that these results can make a contribution by showing that the "One Day One Story" activity can be an effective strategy for increasing interest in reading in young children.